Oxygen‐Deficient Cobalt‐Based Oxides for Electrocatalytic Water Splitting - Ahmed Badreldin (9574341) (2023)
An apparent increased interest has been recently devoted towards the previously untrodden path for anionic point defect engineering of electrocatalytic surfaces. The role of vacancy engineering in improving photo- and electrocatalytic activities of transition metal oxides (TMOs) has been widely reported. In particular, oxygen vacancy modulation on electrocatalysts of cobalt-based TMOs has seen a fresh spike of research work due to the substantial improvements they have shown towards oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Oxygen vacancy engineering is an effective scheme to quintessentially tune the electronic structure and charge transport, generate secondary active surface phases, and modify the surface adsorption/desorption behavior of reaction intermediates during water splitting. Based on contemporary efforts for inducing oxygen vacancies in a variety of cobalt oxide types, this work addresses facile and environmentally benign synthesis strategies, characterization techniques, and detailed insight into the intrinsic mechanistic modulation of electrocatalysts. It is our foresight that appropriate utilization of the principles discussed herein will aid researchers in rationally designing novel materials that can outperform noble metal-based electrocatalysts. Ultimately, future electrocatalysis implementation for selective seawater splitting is believed to depend on regulating the surface chemistry of active and stable TMOs. Other Information Published in: ChemSusChem License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/cssc.202002002